Agomelatine, A Potential Multi-Target Treatment Alternative for Insomnia, Depression, and Osteoporosis in Postmenopausal Women: A Hypothetical Model - Yardimci, Ahmet; Ozdede, Mehmet Ridvan; Kelestimur, Haluk (Frontiers in Psychiatry, 2021)
1 Insomnia, which is associated with menopausal depression, is a common symptom of menopause. Both symptoms have a common etiology, and can affect each other significantly. Pharmacological interventions, including hypnotics and antidepressants, and non‐pharmacological therapies are generally administered in clinical practice for insomnia treatment. As another menopausal disorder, osteoporosis is described as a disease of low bone mineral density (BMD), affecting nearly 200 million women worldwide. Postmenopausal osteoporosis is common among middle-aged women. Since postmenopausal osteoporosis mainly results from low estrogen levels, menopausal hormone therapy (HT) is considered the first-line option for the prevention of osteoporosis during the menopausal period. However, almost no study has evaluated novel treatments for the combined prevention of insomnia, depression, and osteoporosis. Hence, it is necessary to develop new multi-target strategies for the treatment of these disorders to improve the quality of life during this vulnerable period. Melatonin is the major regulator of sleep, and it has been suggested to be safe and effective for bone loss therapy by MT-2 receptor activity. As a result, we hypothesize that agomelatine, an MT-1 and MT-2 receptor agonist and 5-HT2C receptor antagonist, holds promise in the combined treatment of insomnia, depression, and osteoporosis in middle-aged women during menopause.